Designing cantilever dimension for low power wireless applications - Md Rabiul Awal; Muzammil Jusoh; R. Badlishah Ahmad; Thennarasan Sabapathy; M. Najib M. Yasin; Mohd Hafizuddin Mat (Institute of Advanced Engineering and Science, 2019)
This paper presents the effect of cantilever width on the displacement pattern for low power acoustic energy propagation. A single layer cantilever configuration is used to design the harvester with Lead Zirconate Titanate (PZT-5H). The device is designed with 10×(1 to 10)×0.62 mm dimension. The displacements of the cantilever are obtained through the simulation analysis. The maximum displacements are found of 9.80E-28 mm with the smallest width while minimum displacement is found from 5 mm width. From the results, it is obvious that, smaller width can result larger displacements, however, rectangular and square cantilever shape can be advantageous for low power applications.